Hardware realization of DVR with 27 level multi carrier PWM based MLI - Maheswari, M; Thangavel, S (International Journal of Engineering and Technology, 2018)
The quality of the electrical power delivered to consumers is heavily affected by the power electronics based controllers, introduced in both domestic and industrial sectors, which in turn results in malfunctioning of equipment or eventual damage. Series compensators, Shunt compensators and series-shunt compensators are some of the strategies applied to address the power quality issues effectively. In this work a series compensating device, viz. 27 level-cascaded multilevel inverter based Dynamic Voltage Restorer (DVR) with multicarrier SPWM technique is proposed to mitigate voltage swells and voltage sags. The PWM technique used in this work is Alternate Phase Opposition PWM (APODPWM), which is one of the vertical arrangement multicarrier sinusoidal pulse width modulation techniques, to control the cascaded H-bridge inverter. The single-phase version of the proposed system is simulated to verify the effectiveness in addressing voltage issues and it is found that the obtained simulation results are satisfactory. The THD is found to be 3.40%, which is well below IEEE standards apart from considerable improvement in response time. The prototype of the proposed model is developed and the pic-microcontroller PIC16F887 is employed to implement the APODPWM. The experimental results obtained from the prototype are compared with the respective simulation results and they match with reasonable accuracy. Â Â